Rethinking spaces of exception: notes from a forced migrant camp in Jammu and Kashmir. (2016) - Datta, Ankur
In recent years, the camp has emerged as a paradigm of social and political phenomena. This article seeks to engage with the camp as a fact of life and as a framework in the South Asian context. I will first draw on perspectives that have emerged from studies on forced migration and camps in South Asia. I will then draw on anthropological fieldwork I have conducted among Kashmiri Pandits displaced by conflict in the Kashmir valley since 1990, who lived in a displaced persons camp colony in the city of Jammu, Jammu and Kashmir until its closure in 2011. I will try to compare the notion of the state of exception with perspectives from the everyday lives of displaced Kashmiri Pandits, focusing on space and place. I argue that a theoretical framework for studying camps will benefit by paying attention to how forced migrants inhabit a space of 'exception'.